The Validity of Student Worksheet Oriented Blended Learning to Improve Science Literacy Skills in Redox Material - Rahma Aisyah Nur Fadhilah; Rusly Hidayah (Universitas Lampung, 2020)
Student worksheets (LKPD) are a series of learning tools that affect the learning process's optimization. This study aims to describe student worksheets' validity with blended learning orientation to improve students' scientific literacy skills in oxidation-reduction reaction material. The research used is development research with the Nieveen development method with two stages: preliminary research and prototyping. The validity of the LKPD was obtained from the validation assessment of three expert validators in chemistry, namely two chemistry lecturers and one chemistry teacher. The instrument used was a LKPD validation sheet. The evaluation of the validation results of the LKPD showed that the percentage of content validity was 81.7%, and the construct validity was 84.7%. Thus, this study's results indicate that student worksheets with blended learning orientation to training scientific literacy skills can be declared valid.